The role of social cohesion in the implementation and coverage of a mass drug administration trial for malaria control in the Gambia: An in-depth comparison of two intervention villages. (December 2021) - Fehr, Alexandra; Muela, Joan; Nieto-Sanchez, Claudia; Manneh, Ebrima; Baldeh, Dullo; Ceesay, Omar; Bardají, Azucena; Zuiderent-Jerak, Teun; Bunders-Aelen, Joske
Abstract: Mass drug administration (MDA), used increasingly in malaria eradication efforts, involves administering medication to an entire target population regardless of individual-level disease status. This strategy requires high levels of coverage and compliance. Previous studies have assessed individual and structural factors affecting MDA coverage, but there is a need to better understand the influence and expressions of community dynamics and social structures, such as social cohesion. We conducted a social science study concurrent to an MDA clinical trial for malaria control in The Gambia; ethnographic research was conducted prior to, throughout, and between MDA implementation July–November 2018, January–March 2019, and July–November 2019. We assessed how social cohesion, as expressed by the trial population, affects trial coverage through an in-depth ethnographic analysis of two trial villages, using observations, interviews, and focus group discussions with community members who took the trial medication and those who did not. We found that the villages had unique expressions of social cohesion. This was reflected through community participation in the trial implementation and may have affected coverage and compliance. The village with low coverage expressed a form of social cohesion where members followed advice to participate through a hierarchal system but did not actively participate in the MDA or its implementation. The village with high coverage expressed social cohesion as more participatory: individuals took the directive to participate but contextualized the trial implementation to their needs and wants. We analyze these different expressions of social cohesion and the important differences they make for the coverage and compliance levels reached in the two different villages. Highlights: MDA research does not explore heterogeneous social dynamics in implementation outcomes. Focusing on barriers/facilitators for implementation is a grossly utilitarian approach. Trial villages greatly differ in enactment of social dynamics, including social cohesion. Engaging epistemological stances from intervention communities is a must to decolonize bio-ethics research.